2014
DOI: 10.1002/anie.201405023
|View full text |Cite
|
Sign up to set email alerts
|

1,3‐Dehydro‐o‐Carborane: Generation and Reaction with Arenes

Abstract: Like the importance of benzyne, witnessed in modern arene chemistry for decades, 1,2-dehydro-o-carborane (o-carboryne), a three-dimensional relative of benzyne, has been used as a synthon for generating a wide range of cage, carbon-functionalized carboranes over the past 20 years. However, the selective B functionalization of the cage still represents a challenging task. Disclosed herein is the first example of 1,3-dehydro-o-carborane featuring a cage C-B bond having multiple bonding characters, and is success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 51 publications
1
37
0
3
Order By: Relevance
“…[13] The highly polarized CÀBm ultiple bond can also rationalizet hat the selectivity of the CÀHb onds in the ene reactions follows the order:p rimary CÀH > ,s econ- www.chemeurj.org dary CÀH > ,a nd tertiaryC ÀH, which is well in agreement with the acidity of theseC ÀHp rotons. [17] In support of this observation, substrate 6m processing aC F 3 substituent was subjected to this reaction.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…[13] The highly polarized CÀBm ultiple bond can also rationalizet hat the selectivity of the CÀHb onds in the ene reactions follows the order:p rimary CÀH > ,s econ- www.chemeurj.org dary CÀH > ,a nd tertiaryC ÀH, which is well in agreement with the acidity of theseC ÀHp rotons. [17] In support of this observation, substrate 6m processing aC F 3 substituent was subjected to this reaction.…”
mentioning
confidence: 62%
“…In this regard, our recently reported1 ,3-dehydro-o-carborane (2), [13] featuring ap olarized cage C-B multiple bond, would be an excellent candidate for ene reactions with alkenes and alkynes. Herein, we report ag eneral,h igh-yielding, and regioselective ene reaction of 1,3-dehydro-o-carborane for the straightforward access to cage B(3)-substituted carboranyl alkenes and allenes (Scheme 1).…”
mentioning
confidence: 99%
“…1) is the most widely M a n u s c r i p t 2 investigated one, probably due to its commercial availability. One important feature of o-carboranes is that they can undergo dehydrogenation to form 1,2-dehydro-o-carboranes (o-carborynes) [3] or 1,3-dehydro-o-carborane [4], two very reactive intermediates featuring a cage C−C or C−B multiple bond, respectively. These two intermediates can be regarded as three-dimensional relatives of 1,2-dehydrobenzene (benzyne).…”
Section: Introductionmentioning
confidence: 99%
“…During our exploration, we found that o-carboryne exists in two resonance forms, a bonding form vs a biradical form [3d], whereas 1,3-dehydro-o-carborane is best described as a resonance hybrid of a bonding form and a zwitterionic form ( Fig. 1) [4]. o-Carboryne was first reported by Jones in 1990 [3a] and many reactivity studies have been published since then [3d].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation